Respuesta :
5x+3y=12
2x+y=5
Change the second equation to y=-2x+5. Now substitute this into the first equation:
5x+3(-2x+5)=12
5x-6x+15=12
-x+15=12
-x=-3
x=3
Now you can find y.
y=-2x+5
y=-2(3)+5
y=-1
2x+y=5
Change the second equation to y=-2x+5. Now substitute this into the first equation:
5x+3(-2x+5)=12
5x-6x+15=12
-x+15=12
-x=-3
x=3
Now you can find y.
y=-2x+5
y=-2(3)+5
y=-1
I will use the substitution method, but you can also use elimination and matrix.
1. Solve for y in 2x+y=5
2x+y=5
y=5-2x
2. Substitute y=5-2x into 5x+3y=12
5x+3y=12
5x+3(5-2x)=12
5-x=12
3. Solve for x in 15-x=12
15-x=12
-x=12-15
-x=-3
x=3
4. Substitute x=3 into y=5-2x
y=5-2x
y=5-2*3
y=-1
5. Therefore,
x=3
y=-1
Have a nice day :D
1. Solve for y in 2x+y=5
2x+y=5
y=5-2x
2. Substitute y=5-2x into 5x+3y=12
5x+3y=12
5x+3(5-2x)=12
5-x=12
3. Solve for x in 15-x=12
15-x=12
-x=12-15
-x=-3
x=3
4. Substitute x=3 into y=5-2x
y=5-2x
y=5-2*3
y=-1
5. Therefore,
x=3
y=-1
Have a nice day :D